First record of Cobia (Rachycentron canadum) (Pisces: Rachycentridae) at the coast of Madeira Island (NE Atlantic Ocean - Wirtz, Peter (2020)
The Cobia Rachycentron canadum is recorded from Madeira Island for the first time. An individual of this species was encountered and video-documented while SCUBA-diving in about 12 m depth at the south coast of this island.